The Influence of Weathering, Water Sources, and Hydrological Cycles on Lithium Isotopic Compositions in River Water and Groundwater of the Ganges–Brahmaputra–Meghna River System in Bangladesh - Yoshimura, Toshihiro; Araoka, Daisuke; Kawahata, Hodaka; Hossain, H. M. Zakir; Ohkouchi, Naohiko (Frontiers in Earth Science, 2021)
The silicate weathering of continental rocks plays a vital role in determining ocean chemistry and global climate. Spatiotemporal variations in Li isotope ratio (δ7Li) in terrestrial waters identify regimes of current and past weathering processes. Here we examine (1) monthly dissolved δ7Li variation in the Ganges River’s lower reaches, and (2) spatiotemporal variation of river water of the Brahmaputra, Meghna rivers, and groundwater in Bangladesh. From the beginning to maximum flood discharges of the rainy season (i.e., from June to September), Li concentrations and δ7Li in the Ganges River show remarkable changes, with a large influence from the Himalayan sources. However, most Li discharge across the rainy season is a steady-state condition and strongly influenced by the secondary mineral formation in the low-altitude floodplain. Secondary mineral formation strongly influences the Meghna River's Li isotopic composition along with fractionation lines similar to the Ganges River. A geothermal input is an additional Li source for the Brahmaputra River. For groundwater samples shallower than ~60 m depth, both δ7Li and Li/Na are highly scattered regardless of the sampling region, suggesting the variable extent of fractionation. For deep groundwater (70–310 m) with a long residence time of about 3,000 to 20,000 years, the lower δ7Li values indicate more congruent weathering. These results suggest that Li isotope fractionation in rivers and groundwater depends on the timescale of water-mineral interaction, which plays an essential role in determining the isotopic signature of terrestrial Li inputs to the ocean.